Analysis of reactive oxygen species and antioxidant defenses in complex I deficient patients revealed a specific increase in superoxide dismutase activity - Wani, Aijaz A.; Rangrez, Ashraf Y.; Kumar, Himanshu; Bapat, Sharmila A.; Suresh, C. G.; Barnabas, Shama; Patole, Milind S.; Shouche, Yogesh (Free Radical Research, 2008)
The mechanism of free radical production by complex I deficiency is ill-defined, although it is of significant contemporary interest. This study studied the ROS production and antioxidant defenses in children with mitochondrial NADH dehydrogenase deficiency. ROS production has remained significantly elevated in patients compared to controls. The expression of all antioxidant enzymes significantly increased at mRNA level. However, the enzyme activities did not correlate with high mRNA or protein expression. Only the activity of superoxide dismutase (SOD) was found to correlate with higher mRNA expression in patient derived cell lines. The activities of the enzymes such as glutathione peroxidase (GPx), Catalase (CAT) and glutathione-S-transferase (GST) were significantly reduced in patients (p < 0.05 or p < 0.01). Glutathione reductase (GR) activity and intracellular glutathione (GSH) levels were not changed. Decreased enzyme activities could be due to post-translational or oxidative modification of ROS scavenging enzymes. The information on the status of ROS and marking the alteration of ROS scavenging enzymes in peripheral lymphocytes or lymphoblast cell lines will provide a better way to design antioxidant therapies for such disorders.
Keywords: antioxidant enzymes; mitochondrial complex I; mitochondrial myopathies; Reactive Oxygen Species (ROS)

Mechanism of action of novel synthetic dodecapeptides against Candida albicans - Maurya, Indresh Kumar; Thota, Chaitanya Kumar; Sharma, Jyotsna; Tupe, Santosh Genba; Chaudhary, Preeti; Singh, Manoj Kumar; Thakur, Indu Shekhar; Deshpande, Mukund V.; Prasad, Rajendra; Chauhan, Virander Singh (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Three de novo designed low molecular weight cationic peptides (IJ2, IJ3 and IJ4) containing an unnatural amino acid alpha,beta-didehydrophenylalanine (APhe) exhibited potent antifungal activity against fluconazole (FLC) sensitive and resistant clinical isolates of Candida albicans as well as non-albi cans and other yeast and filamentous pathogenic fungi. In the present study, their synthesis, susceptibility of different fungi and the mechanism of anti-candidal action have been elucidated. Methods: The antimicrobial peptides (AMPs) were synthesized by solid-phase method and checked for antifungal activity against different yeasts and fungi by broth microdilution method. Anti-candidal mode of action of the peptides was investigated through detecting membrane permeabilization by confocal microscopy, Reactive Oxygen Species (ROS) generation by fluorometry, apoptosis and necrosis by flow cytometry and cell wall damage using Scanning and Transmission Electron Microscopy. Results and conclusions: The MIC of the peptides against C. albicans and other yeast and filamentous fungal pathogens ranged between 3.91 and 250 mu M. All three peptides exhibited effect on multiple targets in C. albi cans including disruption of cell wall structures, compromised cell membrane permeability leading to their enhanced entry into the cells, accumulation of ROS and induction of apoptosis. The peptides also showed synergistic effect when used in combination with fluconazole (FLC) and caspofungin (CAS) against C. albi cans. General significance: The study suggests that the AMPs alone or in combination with conventional antifungals hold promise for the control of fungal pathogens, and need to be further explored for treatment of fungal infections. (C) 2013 Elsevier By. All rights reserved.
Keywords: Antifungal peptide; Antimicrobial peptide (AMP); Apoptosis; Candida albicans; Reactive Oxygen Species (ROS)

Novel pyrazole derivatives as inhibitors of Leishmania donovani: an integrated approach combining in vitro analysis and mechanistic insights - Kumari, Diksha; Kour, Jaspreet; Kumar, Anuj; Sangral, Monica; Singh, Shashank K.; Sawant, Sanghapal D.; Singh, Kuljit (Bioorganic Chemistry, 2025)
Leishmaniasis is a neglected tropical disease that continues to be a global public health problem, leading to a disastrous impact on poor rural people. The present therapeutic arsenal faces the limitations of drug resistance and toxicity concerns, raising a great need to identify novel chemical scaffolds that are potent, non-toxic, and cost-effective. Heterocycles comprise a distinctive class of molecules exhibiting a wide array of physical, chemical, and biological characteristics and occupy a prominent position in pharmaceutical applications. In the present study, we aimed to investigate three series of pyrazole derivatives synthesized previously by our group for their anti-leishmanial potential against Leishmania donovani parasites. Primarily, 29 compounds were evaluated using an Alamar blue dye-based assay for their inhibitory potency, out of which six molecules (4a, 4b, 4c, 4j, 7a, and 7d) were active with >50 % growth inhibition at a 50 mu M dose. Among them, three molecules (4b, 4j, and 7d) showed remarkable leishmanicidal potency with 50 % inhibitory concentration (IC50) in the range of 5 to 13 mu M. Toxicity analysis revealed that the potential hit (4j) represented a promising cytocompatibility profile along with noteworthy activity against L. donovani intracellular amastigotes. Furthermore, the in-depth mechanistic evaluation using scanning electron microscopy, reactive oxygen species (ROS) generation, mitochondrial membrane potential (Delta Psi m) determination, ATP quantification, cell cycle analysis, and lipid accumulation assay confirms the inhibitory potential of compound 4j. Thus, the present study represents pyrazole derivatives as a potential scaffold for the development of novel chemotherapeutics against leishmaniasis.
Keywords: Cell death; drug discovery; FACS analysis; leishmaniasis; Pyrazole derivatives; Reactive Oxygen Species (ROS); scanning electron microscopy